Electronic transmutation concept: is the inverse process possible? an evaluation of main group compounds - Báez Grez, Rodrigo.; Yáñez Osses, Osvaldo Andrés.; Pino Ríos, Ricardo. (American Chemical Society, 2022)
The electronic transmutation (ET) concept states that when an element with atomic number Z gains an electron, it transmutes into a Z + 1 element, leading to species that possess similar chemical bonding patterns and geometric structures regarding the original (Z + 1) element. In this work, the opposite concept, that is, the inverse ET, is assessed. For this purpose, several main group compounds have been analyzed in terms of the adaptive natural density partitioning. The obtained results suggest that when an atom Z loses an electron, it transmutes into a Z - 1 atom, acquiring its geometrical structure and bonding pattern.